AN ANALYSIS OF LINGUISTIC FEATURES IN THE JAKARTA’S GOVERNOR ELECTION DEBATE 2017 - Pinta Indriani Indriani; Fitrawati Fitrawati (English Language and Literature, 2018)
The purpose of this research is to analyze  linguistic features of political language used by candidates of governor and deputy governor of’ Jakarta in election campaign debate 2017. This research used the descriptive qualitative method. Data of this research are the transcription of debate between three couples of candidates that happens during election campaign debate. The duration of  debates is six hours, which is each of debate has six segments with different time. This data were analyzed based on Beard (2000) theory about linguistic features to persuade and influence citizens for supporting them in election. There are some lingusitc features were found in this research; they are metaphor, analogy, repetition and antithesis. The result of this study showed that not all of utterances used linguistic features. The data from debates are 41 datum. The first candidate (AHY) used 5 metaphor (56%), 3 repetition (33%), and 1 antithesis (11%). The second candidate (AHK) used 3 metaphor (23%), 4 analogy (31%), 4 repetition (31%) and 2 antithesis (15%). While the third candidate (ANS) used 1 metaphor (5%), 2 analogy (26%), 10 repetition (53%), 2 antithesis (16%). From the result of the study were known that the most widely linguistic feature used is repetition 17 times (41%).